“WITH FIRE AND SWORD” BY HENRYK SIENKIEWICZ IN UKRAINIAN CRITICISM OF LATE XIX – EARLY XX CENTURY - Васьків , Микола (Кафедра полоністики Навчально-наукового інституту філології Київського національного університету імені Тараса Шевченка, 2024)
The article analyzes the reception of Henryk Sienkiewicz’s novel “With Fire and Sword” in Ukrainian scientific and literary-critical publications end XIX – beg. XX century, as well as in the responses to these publications by Ukrainian, Polish and Russian researchers, publicists and journalists, who determined for more than a century the attitude of Ukrainians to the Polish writer and his work. The leading role in shaping the all-Ukrainian perception of the work was played by Volodymyr Antonovych’s article in “Kiyevskaya starina” (1886), which stated that “With Fire and Sword” is a novel negatively prejudiced against Ukrainians and this negation is due to historical, ethnographic, toponymic, etc. inaccuracies. Most Ukrainian reviewers of Antonovych’s article (unknown author in “Dilo”, I. Novytskyi in “Slovo”, unknown author in “Bukovyna”) and well-known Russian scholar A. Pypin supported the main provisions of the article by the Ukrainian historian. On the basis of these publications, a tradition was established to evaluate the novel “With Fire and Sword” through the prism of history, a “true”/“false” reproduction of the events of the past and, as a result, to avoid the novel by silence through the negative portrayal of Ukrainians, Cossacks and its leaders attributed to H. Sienkiewicz. He tried to find a compromise between the Polish chauvinistic-xenophobic interpretation of the novel “With Fire and Sword” and its Ukrainian interpretation in the spirit of V. Antonovych Olgerd Górka (1934), relying on “reliable” historical sources and his equally benevolent attitude towards Poles and Ukrainians, which he attributed to the Polish writer. Kharkiv professor Lev Shepelevych (1904) tried to be neutral in defining the achievements and shortcomings of H. Sienkiewicz’s novel in an article about the writer for the Brockhaus and Efron Encyclopedic Dictionary. The collection on the life and work of the Polish novelist (1904), initiated by the well-known Odessa lawyer, literary critic and collector Alexander Femelidi, in which the author was not mentioned and which combined the repetition of the main provisions of the works of V. Antonovych, A. Pypin and, especially, L. Shepelevich, was initiated compilative. Instead, extremely negative were the assessments of the novel “With Fire and Sword” and Sienkiewicz’s work in the article by the Moskvophile Lev Burenin (“Galichanin”, 1904), who chose the devastating criticism of universally recognized authoritative writers as a way of self-affirmation in science and journalism. Most researchers noted the anti-Ukrainian ideological bias of the novel “With Fire and Sword”, which was compensated by the emotionality, plot intrigue of the work and high artistic skill of the author.

У статті аналізується рецепція роману Генрика Сенкевича «Вогнем і мечем» в українських наукових і літературно-критичних публікаціях к. ХІХ – поч. ХХ ст., а також у відгуках на ці публікації українських, польських і російських дослідників, публіцистів і журналістів. Провідну роль у формуванні загальноукраїнського сприйняття твору відіграла стаття Володимира Антоновича в «Киевской старине» (1886 р.), в якій стверджувалося, що «Вогнем і мечем» є негативно упередженим щодо українців романом і ця неґація зумовлена історичними, етнографічними, топонімічними тощо неточностями. Більшість українських рецензентів статті Антоновича та відомий російський науковець О. Пипін повністю підтримали українського історика. Спробував знайти компроміс між польською інтерпретацією роману «Вогнем і мечем» та українським його тлумаченням у дусі В. Антоновича Ольґерд Ґурка (1934), спираючись на «достовірні» історичні джерела та однаково доброзичливе ставлення до поляків і українців. Намагався бути нейтральним у визначенні здобутків і недоліків роману Г. Сенкевича харківський професор Лев Шепелевич (1904). Компілятивним був одеський збірник про життя і творчість польського романіста (1904). Натомість всуціль негативними були оцінки роману «Вогнем і мечем» та творчості Сенкевича загалом у статті москвофіла Лева Буреніна («Галичанин», 1904). Більшість дослідників відзначали антиукраїнську ідейну заанґажованість роману «Вогнем і мечем», яка компенсувалася емоційністю, сюжетною інтригою твору та високою художньою майстерністю автора.
«ВОГНЕМ І МЕЧЕМ» ГЕНРИКА СЕНКЕВИЧА В УКРАЇНСЬКІЙ КРИТИЦІ К. ХІХ – ПОЧ. ХХ СТОЛІТТЯ
Keywords: Henryk Sienkiewicz; literary and cultural Ukrainian-Polish relations; reception; historical novel; historicity/artistry; літературні й культурні українсько-польські взаємини; рецепція; історичний роман; історичність/ художність; Генрик Сенкевич